Triamcinolone-loaded nanocarriers: a novel strategy to mitigate cognitive and emotional sequelae induced by traumatic brain injury via modulation of oxidative stress - Marcotti, Aída; De la Fuente, Sofía; Formica, María Lina; Montivero, Agustín Jorge; Ramires, Martina; Romero, Verónica Leonor; Constantin, María Florencia; Silvero, María Jazmín; Becerra, María Cecilia; Calfa, Gastón Diego; Virgolini, Miriam Beatriz; Palma, Santiago Daniel; et al. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionTraumatic brain injury is the leading cause of death and disability in individuals under 40 years old. It induces various neuropathological outcomes, including cognitive, emotional, and physiological deficits, likely linked to early neuroinflammatory processes. In an animal model, mild traumatic brain injury (mTBI) has been shown to elevate oxidative stress biomarkers, such as advanced oxidation protein products (AOPP) and malondialdehyde (MDA), which persist for over a week. Despite extensive research on anti-inflammatory and neuroprotective therapies, most preclinical and clinical studies report limited efficacy. Synthetic glucocorticoids offer potential for early treatment of TBI-induced neuroinflammation, but clinical use is hindered by adverse effects and poor central nervous system biodistribution. Triamcinolone possesses anti-inflammatory, anti-angiogenic, and microglial inhibitory properties, although it has poor solubility and limited blood-brain barrier (BBB) penetration. Lipid nanocapsules (LNCs) may enhance TR solubility, bioavailability, BBB permeation, and intracellular delivery. This study aimed to evaluate the efficacy of triamcinolone-loaded LNCs (NT) on oxidative stress and cognitive-emotional outcomes following mTBI.MethodsAdult male Wistar rats were subjected to closed-head mTBI via a 45 g weight-drop method, under anesthesia. Animals received NT, conventional triamcinolone, or empty LNCs, 15 minutes and 24 hours post-injury. They were sacrificed 24 hours, 1 or 7 days later for biochemical analysis of AOPP, MDA, and antioxidant enzymes (catalase and superoxide dismutase) activity in the hippocampus, prefrontal, and motor cortices. Separate cohorts underwent behavioral tests assessing memory (novel object recognition, Y-maze, and fear conditioning), 7 days after mTBI.ResultsmTBI induced significant impairments in recognition memory and fear retention, as well as increased AOPP, MDA, and CAT activity. SOD levels peaked at 24 h and normalized by day 7. NT, but not conventional TR, effectively prevented behavioral deficits and normalized OS markers. Importantly, early NT treatment reduced CAT overactivation at 7 days.DiscussionThis study provides the first evidence of the efficacy of NT in mitigating cognitive and emotional sequelae following mTBI, likely through enhanced brain delivery and early modulation of oxidative stress pathways.